THE EFFECT OF JOB SATISFACTION AND CAREER DEVELOPMENT ON EMPLOYEES' ORGANIZATIONAL COMMITMENT AT PT BANK ACEH KCU BANDA ACEH - Tarmizi tar; Vilzati; Leni Marlina; Mega Sulastri (STMIK Indonesia Banda Aceh, 2026)
The purpose of this study was to examine the effect of Job Satisfaction and Career Development on Employees' Organizational Commitment at PT Bank Aceh KCU Banda Aceh, both partially and simultaneously. The study involved 61 respondents as the research sample. This research employed a quantitative method. The data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS (Statistical Package for the Social Sciences). Hypothesis testing was conducted using multiple linear regression analysis, the F-test, and the t-test to determine the simultaneous and partial effects of the independent variables on the dependent variable at a 95% confidence level (α = 0.05). The results of the study indicate that Job Satisfaction has a positive and significant effect on Employees' Organizational Commitment at PT Bank Aceh KCU Banda Aceh, with a t-value of 4.361, which is greater than the t-table value of 1.644. Career Development also has a positive and significant effect on Employees' Organizational Commitment, with a t-value of 2.908, exceeding the t-table value of 1.644. Simultaneously, Job Satisfaction and Career Development have a positive and significant effect on Employees' Organizational Commitment at PT Bank Aceh KCU Banda Aceh, as indicated by an F-value of 15.569, which is greater than the F-table value of 3.00. Based on the simultaneous test, it can be concluded that Job Satisfaction and Career Development significantly influence Employees' Organizational Commitment at PT Bank Aceh KCU Banda Aceh. Furthermore, the partial test results confirm that both Job Satisfaction and Career Development individually have a significant effect on Employees' Organizational Commitment.